Factors affecting psychological health and career choice among medical students in eastern and western region of China after COVID-19 pandemic - Wang, Jingxian; Yang, Chunhua; Wang, Jingzhen; Sui, Xingling; Sun, Wen; Wang, Yue (Frontiers in Public Health, 2023)
Introduction: To unearth superior countermeasures that improve psychological health and upgrade the quality of employment for medical students in China in post-epidemic era, this study was designed to determine the possible factors affecting psychological status and future career choice of this population. Methods: A cross-sectional observational study was carried out. Depression Anxiety Stress Scale-21 (DASS-21) and Insomnia Severity Index (ISI) were applied to measure psychological state. Chi-square and logistic regression analyses were adopted to filtrate related factors for psychological health and employment intention. Results: A total of 936 medical students, including 522 from eastern universities and 414 from western universities, were enrolled in the study. Anxiety among students in China’s western universities was higher than that in China’s eastern universities (30.4% vs 22.0%), but no differences in the occurrences of stress (11.4% vs 13.4%), depression (28.7% vs 24.5%) and insomnia (30.7% vs 25.7%). Grades, academic ranking, household income, attitudes about COVID-19 were associated with the occurrence of psychological problems. In addition, major, education level, academic ranking, family income, and clinical experience may affect the choice of future employment location and employment income. Notably, household income affected by COVID-19 and the perception of epidemic prevention and control resulted in changes in future employment region and income. COVID-19 can lead medical students with psychological problems to have a negative attitude toward future employment. Encouragingly, multiple activities, namely, proactive consideration of employment, taking part in career planning training lectures and timely adjustment of career planning, were beneficial to the professional identity of medical students. Conclusion: This study suggests that medical student psychology is influenced by COVID-19 and academic and financial pressures; actively coping with COVID-19 and making career planning in advance will contribute to optimizing future employment. Our findings provide a potent guideline for relevant departments to accurately adjust job deployment and for medical students to actively choose a career in the future.